Implementasi Matakuliah Pengemasan dan Penyimpanan Pangan : Kemasan Foodgrade - Meiwinda, Eka Rizki; Wijayanti, Willy; Horisanto, Abraham; Hasibuan, Rahmawaty; Dahlan, Andi (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Proper packaging plays a role in protecting food products from physical, chemical and biological damage so that learning about good packaging is needed to ensure food safety. In the implementation of the Food Packaging and Storage course, food grade packaging is applied for use. This community service aims to educate students and the community in food grade food packaging to students of the Agricultural Engineering Technology and Business Department. During the activity, participants actively participate in activities and learn the benefits of using food grade packaging. The result of this community service activity is increased knowledge about food grade packaging.